Militant Democracy and Its Critics - Malkopoulou, Anthoula (Edinburgh University Press, 2019)
Can defensive efforts that curtail rights of participation of antidemocratic movements be consistent with democratic values? In this collection of essays, scholars from across politics, philosophy and law address the unresolved practical and theoretical questions concerning democracy and extremism.